An in situ and rapid self-healing strategy enabling a stretchable nanocomposite with extremely durable and highly sensitive sensing features. Issue 1 (16th November 2020) - Liu, Yang; Fan, Xiangqian; Feng, Weimin; Shi, Xinlei; Li, Fengchao; Wu, Jinhua; Ji, Xinyi; Liang, Jiajie
Abstract : A spontaneous, rapid, and in situ self-healing strategy was proposed to boost both the durability and sensitivity of stretchable strain-sensing materials. Abstract : Progress toward the development of wearable electromechanical sensors with durable and reliable sensing performance is critical for emerging wearable integrated electronic applications. However, it remains a long-standing challenge to realize mechanically stretchable sensing materials with extremely durable and high-performing sensing ability due to the fundamental dilemma lying in the sensing mechanism. In this work, we proposed an in situ and rapid self-healing strategy through nano-confining a dynamic host–guest supramolecular polymer network in a graphene-based multilevel nanocomposite matrix to fabricate a mechanically stretchable and structurally healable sensing nanocomposite which is provided with intriguing sensing durability and sensitivity simultaneously. When repeatedly stretching and releasing the nanocomposite sensing film, the fast association kinetics of cyclodextrin and adamantane host–guest inclusion complexes and good polymer chain dynamics in the supramolecular polymer network endowed by the nanoconfinement effect enable autonomous and rapid repair of the micro-cracks in situ generated in the sensing material. As a result, our strain sensing devices can achieve an extremely high durability and retain stable sensing performance even after over 100 000 stretching-releasing cycles at large strain of 50%. Moreover, the brittle nature originated from the inorganically dominated structure in conjunction with the thermodynamically stable host–guest interactions and dynamic hydrogen bonds inside the multilevel nanocomposite allow the sensing material to exhibit an ultrahigh gauge factor over 1500 with a large working strain of 58%. This work presents a reliable approach for the construction of ultradurable and high-performing wearable electronics.